SOCIAL CHANGE OF THE SOCIETY AS THE RESULT OF THE DECREASING OF RICE QUALITY IN WONOJATI VILLAGE SUB-DISTRICT JENGGAWAH JEMBER DISTRICT - Harun, Sofyan Ade Mustafa; Pradhipta, Mochammad Ivan; Achmad, Umar (SOCA: Jurnal Sosial Ekonomi Pertanian, 2019)
The people in Wonojati Village jenggawah Sub-District are included in fast social change. This codition known from so many new inovation about agriculture that can be adapted by the society. This research disscuss about cause of the decresing of rice Quanlity, the effect from the deceasing of rice quality, and the effort to overcome the problem about the decresing of rice quality. This research use Focus Group Discussion method, with the key informan is the chief of the farmers group, and then use snowball sampling to get another respondent that suitable for the purpose of the research. The result show that the decreasing of rice quality is because of pests and diseases, excessive fertilization, narrowing of waterways and the low education from the people of Wonojati village. The effect of the decresing of rice quality can be seen through economics effect that the farmers income is decreasing and social effect that there are a bad relatins beetwen farmers. The effort that can be done to overcome this decresing of rice quality is to have an agricultural counseling about the using of verification seeds and balanced fertilizations.